Allosteric SHP2 inhibitors in cancer: Targeting the intersection of RAS, resistance, and the immune microenvironment. (June 2021) - Kerr, D. Lucas; Haderk, Franziska; Bivona, Trever G.
Abstract: The nonreceptor protein tyrosine phosphatase SHP2 (encoded by PTPN11 ) integrates growth and differentiation signals from receptor tyrosine kinases (RTKs) into the RAS/mitogen-activated protein kinase (MAPK) cascade. Considered 'undruggable' over three decades, SHP2 is now a potentially druggable target with the advent of allosteric SHP2 inhibitors. These agents hold promise for improving patient outcomes, showing efficacy in preclinical cancer models, where SHP2 is critical for either oncogenic signaling or resistance to current targeted agents. SHP2 inhibition may also produce immunomodulatory effects in certain tumor microenvironment cells to help cultivate antitumor immune responses. The first generation of allosteric SHP2 inhibitors is under clinical evaluation to determine safety, appropriate tolerability management, and antitumor efficacy, investigations that will dictate future clinical applications. Highlights: Allosteric inhibitors stabilize SHP2 in its inactive conformation. SHP2 inhibition shows efficacy in subsets of RTK-, KRAS-, and BRAF-driven cancers. Polytherapy approaches address SHP2-mediated signaling in drug resistance. SHP2 function in T-cells and macrophages suggests immunotherapeutic potential. Phase I/II clinical trials testing allosteric SHP2 inhibitors are ongoing.